(untitled) (Doctor Virtualis, 2023)
This article aims to reflect on how analogy is understood and treated by the class of formal information processing methods that deal with analysing written text. In particular, we consider how machines that ‘understand’ analogies can be constructed. For this purpose, exemplifications from Augustine of Hippo’s De Civitate Dei will be used. The initial investigations carried out on this corpus, albeit limited, lead one to reflect on the theoretical and historiographical significance of the automatic treatment of analogy also in formulating or supporting interpretative hypotheses.